2011
DOI: 10.1002/ptr.3672
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid has an Inhibitory Effect on Pancreatic Lipase and Induces Adipocyte Lipolysis

Abstract: Betulinic acid is a pentacyclic triterpenic acid that exists naturally in many kinds of food and has many biological functions. The present study investigated the antiobesity properties of betulinic acid and possible mechanisms by which betulinic acid functions. To examine the antilipase function of betulinic acid, the ability of betulinic acid to inhibit pancreatic lipase activity in vitro and to prevent the elevation of plasma triacylglycerol levels was tested after oral administration of a lipid emulsion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 9 publications
2
32
0
Order By: Relevance
“…In this study, we also observed a reduction in fat mass of white adipocytes in BA‐treated obese mice. A similar weight loss was also observed in other BA studies (Kim et al, ). Intriguingly, BA treatment elevated the core rectal temperature and the gene expressions of Cidea and Glut4 in BAT in DIO mice, suggesting an enhanced energy expenditure.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we also observed a reduction in fat mass of white adipocytes in BA‐treated obese mice. A similar weight loss was also observed in other BA studies (Kim et al, ). Intriguingly, BA treatment elevated the core rectal temperature and the gene expressions of Cidea and Glut4 in BAT in DIO mice, suggesting an enhanced energy expenditure.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have reported that BA exerts therapeutic effects on obesity and type 2 diabetes (Kim et al, ; Kim, Lee, Kim, & Kim, ); however, few studies have focused on NAFLD, and the underlying molecular mechanism of BA is obscure. We found that BA activated FXR transcriptional activity in a ligand‐driven coactivator manner but had no effect on the other nuclear hormone receptors analysed.…”
Section: Discussionmentioning
confidence: 99%
“…The overall antidiabetic effect of A. roxburghiana could be attributed to multiple effects including the present finding of PTP1B inhibition, insulin secretagogue activity 10 and other effects reported for the active ingredients, betulin and betulinic acid [25][26][27] . Experimental data obtained from our computational insights study further revealed that the C-3 hydroxyl and C-17 carboxylic acid positions of the pentacyclic triterpene skeleton are critical for designing new and better PTP1B inhibitors.…”
Section: Resultssupporting
confidence: 58%
“…Since, some of the compounds identified in the present study were known to occur in A. roxburghiana 25 , our study appears to be the first report on the identification of active compounds against PTP1B principles of the plant. The antidiabetic effect of betulinic acid could also be mediated through other effects including inhibition of pancreatic lipase and adipocyte lipolysis 26 and also by enhancing glucose uptake in adipocytes after long treatment 27 . The PTP1B inhibitory effect of betulin has not been reported before but it is known to improve hyperlipidemia and insulin resistance in experimental animals 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Some of them down-regulated lipid accumulation and insulin induced 3T3-L1 differentiation, reduced adipocyte size, while others decreased the levels of all adipogenic proteins and glucose transporter type 4 (GLUT4), but increased adiponectin (Nishina et al, 2017). Betulinic acid has been reported to have a strong lipolytic effect mediated by cAMP-dependent phosphodiesterase inhibition (Kim et al, 2012). Cucrumin has a certain beneficial effect on regulating glucose and lipid metabolism.…”
Section: In Vitro Studiesmentioning
confidence: 99%